Pengaruh Pestisida Nabati Terhadap Intensitas Serangan Ulat Grayak (Spodoptera litura) Pada Tanaman Kedelai Hitam (Glycine max L.) - Rahmadina ,; M.Idris - -; Rizky Sundari Fitria (BEST Journal (Biology Education, Sains and Technology), 2022)
This study aims to determine the effect of the combination of papaya leaves and basil leaves on the intensity of armyworm pests (Spodoptera litura) on black soybean plants (Glycine max L.). The research was conducted at Dusun 7-B street, Karang Anyar Village, Beringin District, Deli Serdang Regency. The research implementation time was carried out from August to October 2022. The tools used were hoes, measuring cups, blenders, tape measure, sprayers, scissors, filters, barrels/buckets, cell phones and stationery. The materials used are Detam 1 soybean seeds, papaya leaves, basil leaves, and water. The method used is the non-factorial Randomized Block Design (RBD) method, namely by applying pesticides with a combination of papaya leaf and basil leaf pesticides with 4 levels of treatment consisting of: P0 = Control (without treatment), P1 = 100 ml/L (100 ml of pesticide) papaya leaf + basil leaves /L water), P2 = 200 ml/L (200 ml papaya leaf pesticide + basil leaves /L water), P3 = 300 ml/L (300 ml papaya leaf pesticide + basil leaves /L water). The number of replicates in this study was 5 replicates with a spacing of 20 x 40 cm. The research parameter was the attack intensity of the grayworm and was analyzed by ANOVA with a significant number of 5% and continued with the Duncan's Multiple Range Test (DMRT). The results showed that the application of a combination of papaya leaf and basil leaf vegetable pesticides had a very significant effect on the attack intensity of grayworms and the best concentration was at a concentration of 300 ml/L which reduced the intensity of grayworm attacks by up to 13.3% on black soybean plants (Glycine max L.).